COLLABORATIVE GOVERNANCE DALAM MENANGGULANGI BENCANA LONGSOR DI BIDANG PENCEGAHAN DAN KESIAPSIAGAAN DI BPBD KABUPATEN SUMEDANG - Hendra Ali Nugraha; Dadan Setia Nugraha (LPPM UNSAP, 2026)
Sumedang Regency is categorized as an area vulnerable to natural disasters, particularly landslides, due to its geographical characteristics dominated by mountainous terrain and the presence of several active fault lines crossing the region. This study aims to examine how Collaborative Governance is implemented in managing landslide disasters, particularly in the areas of prevention and preparedness carried out by the Regional Disaster Management Agency (BPBD) of Sumedang Regency. The study also explores the inhibiting factors and efforts made to overcome these obstacles. Informants in this study include various stakeholders involved in the collaboration, such as Basarnas, the Indonesian National Armed Forces (TNI), and the National Police (Polri), as well as other relevant parties. The research method used is qualitative, with data collection techniques including literature study and field research through observation, interviews, and documentation. The data analysis procedure includes data reduction, data presentation, verification, and triangulation. The results show that the implementation of Collaborative Governance in landslide disaster management in Sumedang Regency is generally quite good, although it still faces several challenges, such as limited resources, lack of public knowledge, limited collaboration forums, weaknesses in regulatory support, and suboptimal face-to-face communication and coordination. Efforts to address these challenges include improving public awareness of disaster risks, strengthening inter-agency communication, and encouraging more responsive and innovative leadership.